Preliminary study on the cryopreservation of Calanoid Copepod Acartia tsuensis embryos. - Lee, Jennifer Abao
The toxicity test using dimenthyl sulfoxide (DMSO) at 5, 10, 15 and 20 concentrations on Acartia tsuensis eggs at cleavage, early and late naupliar stages was studied. Highest survival up to hatching stage was observed in the early and late naupliar stages at 5 and 10 DMSO concetrations. The embryos that survived were then frozen at -20 degrees centigrade and -80 degrees centigrade. Observations showed that early naupliar embryos treated with 5 and 10 DMSO survived best when cryopreserved at -20 degrees centigrade, while freezing at -80 degrees centigrade ressulted to the total mortality of embryos because of intracellular freezing.